United we stand, divided we rule: how political polarization erodes democracy. Issue 2 (17th February 2021) - Arbatli, Ekim; Rosenberg, Dina
ABSTRACT: Although there is a broad consensus among political scientists that polarization is detrimental to democracy, very few empirically investigate the links between political polarization and democratic erosion. Most studies use diversity measures that fail to capture contemporary polarization, where the society is divided into two large hostile camps. In this article, we address the gap. Theoretically, we argue that polarization increases animosity between "enemy camps, " making voters more willing to accept anti-democratic measures against the rival group. This tacit approval becomes even more pronounced during election periods, where political controversy reigns and the stakes are higher. Focusing on a specific type of electoral manipulation, we hypothesize that ceteris paribus, political polarization is strongly associated with higher levels of government intimidation of the opposition. We expect this relationship to be stronger in democracies than in autocracies. Empirically, we create our own measure of political polarization based on Esteban and Ray's widely accepted measure, and test our hypotheses on panel data. In addition to the regression analysis, we offer anecdotal evidence from Turkey, Hungary, and the United States.